Developing U PPAAL over 15 years - Behrmann, Gerd; David, Alexandre; Larsen, Kim Guldstrand; Pettersson, Paul; Yi, Wang (Software, practice & experience, 2011)
U PPAAL is a tool suitable for model checking real‐time systems described as networks of timed automata communicating by channel synchronizations and extended with integer variables. Its first version was released in 1995 and its development is still very active. It now features an advanced modeling language, a user‐friendly graphical interface, and a performant model checker engine. In addition, several flavors of the tool have matured in recent years. In this paper, we present how we managed to maintain the tool during 15 years, its current architecture with its challenges, and we give the future directions of the tool. Copyright © 2011 John Wiley & Sons, Ltd.